Mile-high views : surveying the serials vista : NASIG 2006 : proceedings of the North American Serials Interest Group, Inc. 21st Annual Conference May 4-7, 2006 Denver, Colorado /: surveying the serials vista : NASIG 2006 : proceedings of the North American Serials Interest Group, Inc. 21st Annual Conference May 4-7, 2006 Denver, Colorado. (2013) - Unknown
No abstract available